2021
DOI: 10.1186/s12913-021-06762-0
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an algorithm to identify cardiovascular deaths from administrative health records: a multi-database population-based cohort study

Abstract: Background Cardiovascular death is a common outcome in population-based studies about new healthcare interventions or treatments, such as new prescription medications. Vital statistics registration systems are often the preferred source of information about cause-specific mortality because they capture verified information about the deceased, but they may not always be accessible for linkage with other sources of population-based data. We assessed the validity of an algorithm applied to adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Lix et al used a pre-existing cohort of patients receiving antidiabetic medication for their validation and opted for a much broader definition of CV death including, amongst others, death due to hypertensive disease. 16 The overall PPV was 54.5%, ranging from 34% to 73% for individual Canadian provinces. A meta-analysis by Singh et al included five studies, four of which reported PPVs for sudden cardiac death and one for AMI- and stroke-related death.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Lix et al used a pre-existing cohort of patients receiving antidiabetic medication for their validation and opted for a much broader definition of CV death including, amongst others, death due to hypertensive disease. 16 The overall PPV was 54.5%, ranging from 34% to 73% for individual Canadian provinces. A meta-analysis by Singh et al included five studies, four of which reported PPVs for sudden cardiac death and one for AMI- and stroke-related death.…”
Section: Discussionmentioning
confidence: 95%
“…A study based on administrative health records from Canada reported an increase in the PPV if restricting the algorithm of CV death to inpatient deaths with a CV main discharge diagnosis. 16 This study is subject to limitations that need to be considered when interpreting the results. While claims data contain rich information on diagnoses, procedures, and health care received by patients, they lack clinical information like lab values and other diagnostic results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using a large, linked, national health administrative database would allow investigating the incidence of events like opioid use after hospital discharge and the associated predictors on a national level [32]. In another study, a cardiovascular mortality prediction algorithm applied to administrative databases from Canada and UK had moderate validity when compared to vital statistics data [33]. Studies like these provide insights into current safety practices and healthcare utilization patterns outside of the USA.…”
Section: International Registriesmentioning
confidence: 99%
“…Update: Data on cardiovascular-related causes of death will primarily be captured using the following definition: (a) in-hospital (or emergency department) death with a cardiovascular disease diagnosis in the primary/most responsible diagnosis position or (b) out-of-hospital death (including death in an emergency department) without documentation of cancer in the 365 days before and including the date of death and without documentation of trauma in the 30 days before and including the date of death. 2 A death in the emergency department with a cardiovascular event as the primary diagnosis will be defined as "in-hospital" cardiovascular-related death, regardless of whether they had cancer or trauma code. Justification: We were recently notified of unanticipated delays in the linkage of the Office of the Register General deaths database at ICES, which will now take several more years to cover the entire trial period.…”
mentioning
confidence: 99%